1984
DOI: 10.1056/nejm198403013100902
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity of Chromosome 13 in Retinoblastoma

Abstract: We studied the frequency of chromosome 13 homozygosity in tumor tissue obtained directly from eyes harboring retinoblastomas. The data indicate that approximately half of all retinoblastomas are homozygous for large portions of 13q, that the homozygosity occurs in vivo and not as an event secondary to culture of the tumor cells, that chromosome 13 homozygosity is not correlated with the degree of histopathologic differentiation of the tumor, and that the homozygosity occurs in both sporadic and hereditary reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
65
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(71 citation statements)
references
References 13 publications
5
65
0
1
Order By: Relevance
“…The nature of the deletions which give rise to these abnormal band patterns is illustrated in Figure 2, (Enzinger & Weiss, 1988). The prevalence of individual histological types in our series of 69 primary tumours (Table I) is similar to that reported in the general population (Enzinger & Weiss, 1988) (Cavenee et al, 1983;Dryja et al, 1984;Hansen et al, 1985;Benedict et al, 1987;Toguchida et al, 1988 (Friend et al, 1987) three soft tissue tumours with homozygous RB1 deletions were found. One of these was also in a leiomyosarcoma, one in an MFH and the last case was unclassified.…”
Section: Resultssupporting
confidence: 72%
“…The nature of the deletions which give rise to these abnormal band patterns is illustrated in Figure 2, (Enzinger & Weiss, 1988). The prevalence of individual histological types in our series of 69 primary tumours (Table I) is similar to that reported in the general population (Enzinger & Weiss, 1988) (Cavenee et al, 1983;Dryja et al, 1984;Hansen et al, 1985;Benedict et al, 1987;Toguchida et al, 1988 (Friend et al, 1987) three soft tissue tumours with homozygous RB1 deletions were found. One of these was also in a leiomyosarcoma, one in an MFH and the last case was unclassified.…”
Section: Resultssupporting
confidence: 72%
“…Previous studies indicated that the risk of developing retinoblastoma was linked to abnormalities, including deletions, of the long arm of chromosome 13 (2,7,16,48). Further studies suggested that inactivation of both alleles of a sequence mapping to chromosome 13q14 was a necessary event in the pathogenesis of this tumor, consistent with the notion that this region harbored a tumor suppressor gene (4,40).…”
supporting
confidence: 63%
“…For example, in familial retinoblastoma (RB), patients are heterozygous for an inactivating mutation in the retinoblastoma tumor suppressor gene. RB tumors develop following bi-allelic inactivation of the RB gene (Cavenee et al, 1983;Dryja et al, 1984). As children born with a germline RB mutation require only one additional genetic alteration, the loss of the one remaining functional allele, the incidence of RB tumor formation is much higher and occurs at an earlier age than observed in the general population, where both RB alleles must be inactivated in the same cell for tumors to develop (Knudson, 1971).…”
Section: The Brain As a Specialized Ecosystemmentioning
confidence: 99%